THARIQAH AL-GHINA FII HIFDZI AL-MUFRADAAT WA ATSARUHAA AT-THALIBAH LISSHAFI AL-KHAAMIS FII AL-MADRASAH AL-IBTIDAIYAH “AL-QOLAM” - Lukman Taufik Akasahtia; Muhammad Firnanda; Emnis Anwar (SHAWTUL ARAB, 2021)
The singing method is a learning method that uses singing as a method of learning. Singing or listening to music is part of an individual's natural need. Through singing and music, children's expressive abilities develop and through singing, children will also express all their thoughts and feelings. Singing is also a part of the emotional expression, as through the method of singing students can store good memories and they will have a strong memory especially learning foreign languages such as Arabic. This research aims to identify the impact of the singing style in memorizing vocabulary on students' memory in the primary school "Al-Qalam". The research methodology using the quantitative method. The study population were all fifth grade students in the "Al-Qalam" primary school. Data collection techniques using a questionnaire. The results of this study concluded that there is an effect of the singing method in memorizing vocabulary on the memory of the fifth grade students in the elementary school "Al-Qalam". r number r > table = 12,199 > 0,514 Then Ha is accepted and Ho is rejected.